Composite electrode material for lithium ion battery and preparation process of composite electrode material

By preparing tin oxide coated with heteroatom-doped porous carbon as the negative electrode material for lithium-ion batteries, the problems of low capacity, poor conductivity and volume expansion of existing materials are solved, and high capacity and good cycle stability of the battery are achieved.

CN120709320AInactive Publication Date: 2025-09-26山东省欣安创能新能源有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510854314.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-09-26
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium-ion battery negative electrode materials such as graphite and transition metal oxides have problems such as low capacity, poor conductivity and volume expansion, resulting in poor battery cycle stability and rate performance.

Method used

A carbon-containing composite active material is used, and a carboxyl-terminated polymer is cross-linked with tin chloride to form tin oxide coated with heteroatom-doped porous carbon. The confinement and conductivity of the porous carbon are used to improve the volume expansion of the tin oxide, and nitrogen and sulfur elements are introduced to improve the conductivity and specific capacity.

Benefits of technology

It improves the cycle stability and rate performance of the battery, enhances the capacity performance of the electrode material, shortens the lithium ion transmission path, and increases the energy storage sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120709320A_ABST
    Figure CN120709320A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a composite electrode material for a lithium ion battery and a preparation process of the composite electrode material. The composite electrode material is formed by mixing raw materials including a carbon-containing composite active substance, a conductive agent, a cementing agent and an organic solvent, wherein the carbon-containing composite active substance is tin oxide of which the surface is coated with heteroatom-doped porous carbon, the volume expansion phenomenon of the tin oxide can be relieved by utilizing the confinement effect of the porous carbon, so that the cycle stability of the battery is guaranteed, and after the carbon-containing composite active substance is coated with the porous carbon, the active material shows good conductivity by utilizing the conductivity of the porous carbon material, so that the battery performance is improved. Therefore, the battery can show good rate capability. In addition, the porous carbon material can also provide better conductivity and specific capacity, so that the electrode material can show more excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite electrode material for lithium ion batteries and a preparation process thereof. Background Art

[0002] With the increasing consumption of fossil energy, environmental pollution and energy depletion are becoming increasingly serious. Consequently, the research and development and application of clean energy have become a hot topic. Electricity is the most researched and widely used energy source. Energy storage devices are indispensable for the application of electric energy. Lithium-ion batteries, with their advantages such as high output voltage and high energy density, have gradually emerged as the mainstream energy source.

[0003] Lithium-ion batteries are mainly composed of electrode materials, current collectors, electrolytes and separators. Among them, the performance of lithium-ion batteries has a decisive influence on the capacity and electrochemical properties of lithium-ion batteries. At present, the negative electrode materials of lithium-ion batteries are generally graphite or other carbon materials. Although such negative electrode materials have good conductivity, they have low capacity and cannot meet the use requirements of large-capacity batteries. In recent years, transition metal oxides have been widely studied as negative electrode materials, but they generally have poor conductivity. Moreover, as the number of charge and discharge cycles increases, transition metal oxides will experience severe volume expansion during the continuous lithium ion insertion and extraction process, which will cause pulverization and ultimately cause the battery capacity to seriously decay. Moreover, the conductivity of transition metal oxides is also poor, which will lead to poor cycle stability and rate performance of the battery. Therefore, there are still obvious defects in practical applications.

[0004] Based on this, the present invention provides a composite electrode material with good comprehensive performance, which can be used as a negative electrode material for lithium-ion batteries and solve the problems existing in the prior art. Summary of the Invention

[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a composite electrode material for lithium ion batteries and a preparation process thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A composite electrode material for a lithium-ion battery, comprising the following raw materials in parts by weight:

[0008] 70-80 parts of carbon-containing composite active material, 10-20 parts of conductive agent, 5-10 parts of binder, and 100-120 parts of organic solvent.

[0009] As a further embodiment of the present invention, the method for preparing the carbon-containing composite active material comprises the following steps:

[0010] Step 1: Add the carboxyl-terminated polymer to the ethanol aqueous solution, stir mechanically to mix evenly, then add tin chloride to the resulting mixture, raise the temperature to 50-60°C after the addition, keep stirring for 16-24 hours, stop heating, cool and discharge, filter out the solid material, wash and freeze-dry to obtain an intermediate material;

[0011] Step 2: Add the intermediate material and urea into a tubular furnace, increase the temperature and calcine. After calcination, take out the material, wash and dry it to obtain a carbon-containing composite active material.

[0012] As a further embodiment of the present invention, in step 1, the method for preparing the carboxyl-terminated polymer comprises the following steps:

[0013] Step S1, adding 2,3,6,7,10,11-hexa(4'-aminophenyl)triphenylene to an ethanol aqueous solution having a volume fraction of 70-80%, stirring, and after forming a uniform solution, introducing nitrogen protection, and continuously adding [2,2']-bithiophene-5,5'-dicarbaldehyde under stirring. After the addition is completed, heating is started and the temperature is raised to 70-80°C. After stirring at this temperature for 6-12 hours, heating is stopped, and after cooling to room temperature, a solid material is separated by suction filtration, washed, and dried to obtain a polymer precursor;

[0014] Step S2: Add the polymer precursor to toluene, start stirring after addition, mix evenly, continue to add the acidifying modifier and catalyst, and after addition, increase the temperature to 40-50°C, keep warm for 3-6 hours, cool and discharge the material to obtain a carboxyl-terminated polymer.

[0015] As a further embodiment of the present invention, in step S1, the molar ratio of the 2,3,6,7,10,11-hexa(4'-aminophenyl)triphenylene to [2,2']-bithiophene-5,5'-dicarbaldehyde is 1:2-3.

[0016] As a further embodiment of the present invention, in step S2, the acidifying modifier is any one of maleic anhydride, succinic anhydride or glutaric anhydride.

[0017] As a further embodiment of the present invention, in step S2, the catalyst is p-toluenesulfonic acid.

[0018] As a further embodiment of the present invention, in step 2, the mass ratio of the intermediate material to urea is 1:0.2-0.4.

[0019] As a further solution of the present invention, in step 2, the calcination temperature is 700-800° C. and the calcination time is 1-3 hours.

[0020] In the above technical solution, first, 2,3,6,7,10,11-hexa(4'-aminophenyl)triphenylene and [2,2']-bithiophene-5,5'-dicarboxaldehyde are used as polymerization monomers. The amino groups and aldehyde groups in each other's structures can undergo continuous and uninterrupted Schiff base reaction under high temperature conditions, continuously extending the chain polymerization. By controlling the dosage ratio of the two, the end of the obtained polymer precursor structure can contain active amino substituents. Then, under the action of a catalyst, an acidifying modifier is used to perform carboxyl modification on the active amino groups at the end of the polymer precursor structure to obtain a carboxyl-terminated polymer.

[0021] Then, utilizing the property that the carboxyl groups in the carboxyl-terminated polymer structure can produce cross-linking reactions with high-valent metal ions, tin chloride is used as a metal ion source, and the tin ions generated by its ionization can serve as a cross-linking agent to achieve further cross-linking of the carboxyl-terminated polymer to obtain an intermediate material, which is then stirred and mixed with urea and calcined under high temperature conditions. The rigid ring in the polymer structure can serve as a carbon source, the thiophene ring can provide a sulfur source, and the Schiff base group can provide a nitrogen source. During the calcination process, tin and urea can combine with the oxygen source provided by the oxygen source to form tin oxide, and the polymer will be carbonized to form porous carbon. Nitrogen and sulfur elements will be doped as elements, introducing a defect structure in the porous carbon material to obtain tin oxide coated with heteroatom-doped porous carbon, that is, a carbon-containing composite active material.

[0022] As a further solution of the present invention, the conductive agent is carbon black or acetylene black; the binder is polytetrafluoroethylene; and the organic solvent is N-methylpyrrolidone.

[0023] A preparation process of a composite electrode material for lithium-ion batteries is as follows:

[0024] After weighing all the raw materials according to their mass fractions, they are added into a stirring kettle and stirred until a uniform slurry is formed to obtain a composite electrode material.

[0025] Beneficial effects of the present invention:

[0026] The present invention prepares tin oxide coated with heteroatom-doped porous carbon as the active material in the electrode material. First, the coating of the porous carbon will have a confining effect on the tin oxide, so that the volume expansion phenomenon of the tin oxide during the charge and discharge process is alleviated, thereby ensuring the cycle stability of the battery. Secondly, after being coated with the porous carbon, the conductivity of the porous carbon material can be utilized to make the active material exhibit good conductivity, so that the battery can exhibit good rate performance. In addition, the rich pore structure of the porous carbon material can effectively shorten the transmission path of lithium ions and expose more active lithium storage sites, thereby combining the high capacity of tin oxide to make the electrode material have high capacity performance. In addition, the doping of nitrogen elements can introduce defect sites into the porous carbon, further improving the conductivity and specific capacity of the porous carbon. The doping of sulfur elements can increase the specific surface area of ​​the porous carbon material, so that it can produce more energy storage sites, which is beneficial to the specific capacity of the electrode material.

[0027] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 The figures are scanning electron microscope images and transmission electron microscope images of the carbon-containing composite active material, wherein (A) is a scanning electron microscope image and (B) is a transmission electron microscope image. DETAILED DESCRIPTION

[0030] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0031] Preparation example, preparation of carbon-containing composite active materials:

[0032] Step 1: Add 1.5g of carboxyl terminated polymer to ethanol aqueous solution.

[0033] After the addition is completed, the mixture is mechanically stirred and mixed evenly, and then 0.2g of tin chloride is added to the formed mixture. After the addition is completed, the temperature is raised to 55°C, and the mixture is kept warm and stirred for 18 hours. Then, the heating is stopped, the temperature is lowered, the solid material is filtered out, and the intermediate material is obtained through washing and freeze-drying processes;

[0034] Step 2: Add 1 g of the intermediate material and 0.3 g of urea into a tubular furnace, increase the temperature to 750°C, and calcine for 2 hours. After calcination, take out the material, wash it, and dry it to obtain a carbon-containing composite active material.

[0035] Figure 1 The figures are scanning electron microscope images and transmission electron microscope images of the carbon-containing composite active material, where (A) is a scanning electron microscope image. From (A), it can be seen that it has a rich porous structure. (B) is a transmission electron microscope image. From (B), it can be seen that it is a coated structure.

[0036] The preparation method of the carboxyl-terminated polymer comprises the following steps:

[0037] Step S1, adding 0.1 g of 2,3,6,7,10,11-hexa(4'-aminophenyl)triphenylene to a 70% by volume ethanol aqueous solution, starting stirring, and after a uniform solution is formed, introducing nitrogen protection, and continuing to add 0.06 g of [2,2']-bithiophene-5,5'-dicarbaldehyde under stirring. After the addition is completed, heating is started and the temperature is raised to 75° C. After stirring at this temperature for 9 hours, heating is stopped, and after cooling to room temperature, the solid material is separated by suction filtration, washed, and dried to obtain a polymer precursor;

[0038] Step S2: add 0.3 g of polymer precursor to toluene. After the addition is complete, start stirring and mix evenly. Then, add 0.05 g of maleic anhydride and 0.01 g of p-toluenesulfonic acid. After the addition is complete, raise the temperature to 45°C, keep the temperature for 4 hours, cool and discharge the material to obtain a carboxyl-terminated polymer.

[0039] Example 1: A composite electrode material for a lithium-ion battery, comprising the following raw materials in parts by weight:

[0040] 70 parts of carbon-containing composite active material, 10 parts of conductive agent carbon black, 10 parts of binder polytetrafluoroethylene, and 100 parts of organic solvent N-methylpyrrolidone.

[0041] The preparation process of the electrode material is as follows:

[0042] After weighing all the raw materials according to their mass fractions, they are added into a stirring kettle and stirred until a uniform slurry is formed to obtain a composite electrode material.

[0043] The preparation method of the carbon-containing composite active material is shown in the preparation example, and the same applies to the following.

[0044] Example 2: A composite electrode material for a lithium-ion battery, comprising the following raw materials in parts by weight:

[0045] 75 parts of carbon-containing composite active material, 15 parts of conductive agent carbon black, 10 parts of binder polytetrafluoroethylene, and 100 parts of organic solvent N-methylpyrrolidone.

[0046] The preparation process of the electrode material is as follows:

[0047] After weighing all the raw materials according to their mass fractions, they are added into a stirring kettle and stirred until a uniform slurry is formed to obtain a composite electrode material.

[0048] Example 3: A composite electrode material for a lithium-ion battery, comprising the following raw materials in parts by weight:

[0049] 80 parts of carbon-containing composite active material, 15 parts of conductive agent carbon black, 5 parts of binder polytetrafluoroethylene, and 120 parts of organic solvent N-methylpyrrolidone.

[0050] The preparation process of the electrode material is as follows:

[0051] After weighing all the raw materials according to their mass fractions, they are added into a stirring kettle and stirred until a uniform slurry is formed to obtain a composite electrode material.

[0052] Comparative Example 1: A composite electrode material for a lithium-ion battery, comprising the following raw materials in parts by weight:

[0053] 75 parts of commercially available activated carbon, 15 parts of conductive agent carbon black, 10 parts of binder polytetrafluoroethylene, and 100 parts of organic solvent N-methylpyrrolidone.

[0054] The preparation process of the electrode material is as follows:

[0055] After weighing all the raw materials according to their mass fractions, they are added into a stirring kettle and stirred until a uniform slurry is formed to obtain a composite electrode material.

[0056] The commercially available activated carbon was purchased from Anhui Xingheng Environmental Protection Technology Co., Ltd.

[0057] Comparative Example 2: A composite electrode material for a lithium-ion battery, comprising the following raw materials in parts by weight:

[0058] 75 parts of commercially available tin oxide, 15 parts of conductive agent carbon black, 10 parts of binder polytetrafluoroethylene, and 100 parts of organic solvent N-methylpyrrolidone.

[0059] The preparation process of the electrode material is as follows:

[0060] After weighing all the raw materials according to their mass fractions, they are added into a stirring kettle and stirred until a uniform slurry is formed to obtain a composite electrode material.

[0061] The commercially available tin oxide was purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0062] Test Example: The composite electrode materials in the embodiments of the present invention and the comparative example were evenly coated on the surface of aluminum foil and placed in a drying oven at 80°C. After they were completely dried, they were cut into circular electrode pieces with a diameter of 12 mm. The loading amount was controlled to be approximately 0.8 mg. The electrode pieces were used as working electrodes, a metal lithium sheet was used as a counter electrode, a Celgard 2325 microporous membrane was used as the diaphragm, and the electrolyte was LiPF6 (1 mol / L) as the solute and ethylene carbonate and diethyl carbonate (volume ratio of 1:1) as the solvent. The cells were assembled into button cells in an argon-filled glove box and subjected to electrochemical performance tests. The results are shown in the following table:

[0063] Table 1

[0064] Specific capacity (mAh / g) Capacity retention after 50 cycles (%) Example 1 612.4 98.7 Example 2 612.9 99.1 Example 3 612.7 99.0 Comparative Example 1 374.1 97.8 Comparative Example 2 559.4 84.5

[0065] Note: The current density during the above test is 0.1 A / g.

[0066] According to the test results, the composite electrode material prepared in the embodiment of the present invention has significantly better specific capacity and cycle stability performance. After replacing the carbon-containing composite active material with commercially available activated carbon, although the cycle stability can still maintain a high level, the high specific capacity provided by tin oxide is lost, resulting in a sharp decrease in the specific capacity of the battery. After replacing the carbon-containing composite active material with commercially available tin oxide, the specific capacity performance is acceptable, but due to the severe volume expansion effect, the cycle stability is greatly reduced.

[0067] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal description of the claims, or if they include equivalent structural elements that are not substantially different from the literal description of the claims, then these other embodiments should also be included in the scope of the claims.

[0068] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A composite electrode material for lithium-ion batteries, characterized in that: According to parts by weight, it includes the following raw materials: 70-80 parts of carbon-containing composite active material, 10-20 parts of conductive agent, 5-10 parts of binder, and 100-120 parts of organic solvent.

2. A composite electrode material for lithium-ion batteries according to claim 1, characterized in that: The method for preparing the carbon-containing composite active material comprises the following steps: Step 1: Add the carboxyl-terminated polymer to the ethanol aqueous solution, stir mechanically to mix evenly, then add tin chloride to the resulting mixture, raise the temperature to 50-60°C after the addition, keep stirring for 16-24 hours, stop heating, cool and discharge, filter out the solid material, wash and freeze-dry to obtain an intermediate material; Step 2: Add the intermediate material and urea into a tubular furnace, increase the temperature and calcine. After calcination, take out the material, wash and dry it to obtain a carbon-containing composite active material.

3. A composite electrode material for lithium-ion batteries according to claim 2, characterized in that: In step 1, the method for preparing the carboxyl-terminated polymer comprises the following steps: Step S1, adding 2,3,6,7,10,11-hexa(4'-aminophenyl)triphenylene to a 70-80% by volume ethanol aqueous solution, starting stirring, and after a uniform solution is formed, introducing nitrogen protection, and continuously adding [2,2']-bithiophene-5,5'-dicarbaldehyde under stirring. After the addition is completed, heating is started and the temperature is raised to 70-80°C. After stirring at this temperature for 6-12 hours, heating is stopped, and after cooling to room temperature, a solid material is separated by suction filtration, washed, and dried to obtain a polymer precursor; Step S2: Add the polymer precursor to toluene, start stirring after addition, mix evenly, continue to add the acidifying modifier and catalyst, and after addition, increase the temperature to 40-50°C, keep warm for 3-6 hours, cool and discharge the material to obtain a carboxyl-terminated polymer.

4. A composite electrode material for lithium-ion batteries according to claim 3, characterized in that: In step S1, the molar ratio of the 2,3,6,7,10,11-hexa(4'-aminophenyl)triphenylene to [2,2']-bithiophene-5,5'-dicarbaldehyde is 1:2-3.

5. The composite electrode material for lithium-ion batteries according to claim 2, characterized in that: In step S2, the acidifying modifier is any one of maleic anhydride, succinic anhydride or glutaric anhydride.

6. A composite electrode material for lithium-ion batteries according to claim 2, characterized in that: In step S2, the catalyst is p-toluenesulfonic acid.

7. The composite electrode material for lithium-ion batteries according to claim 2, characterized in that: In step 2, the mass ratio of the intermediate material to urea is 1:0.2-0.

4.

8. The composite electrode material for lithium-ion batteries according to claim 2, characterized in that: In step 2, the calcination temperature is 700-800° C. and the calcination time is 1-3 hours.

9. The composite electrode material for lithium-ion batteries according to claim 1, characterized in that: The conductive agent is carbon black or acetylene black; the binder is polytetrafluoroethylene; and the organic solvent is N-methylpyrrolidone.

10. A process for preparing a composite electrode material for a lithium-ion battery according to claim 1, characterized in that: The preparation process is as follows: After weighing all the raw materials according to their mass fractions, they are added into a stirring kettle and stirred until a uniform slurry is formed to obtain a composite electrode material.